Migraine diagnosis and treatment: A knowledge and needs assessment among primary care providers. (April 2016) - Minen, Mia T; Loder, Elizabeth; Tishler, Lori; Silbersweig, David
Background: Studies reveal that migraine is often under-recognized, misdiagnosed and inadequately treated in the primary care setting. Objective: The objective of this article is to assess primary care providers' (PCP) knowledge and needs regarding migraine diagnosis and management. Methods: We held semi-structured group interviews and distributed a brief questionnaire to PCPs in our hospital network. Building on the information from the interviews, we developed a comprehensive survey assessing PCPs' knowledge about migraine. Descriptive analyses were performed. Results: The initial interviews and brief questionnaires revealed that PCPs are aware of the prevalence of migraine but are uncertain about the details of management. Eighty-three of 120 physicians completed the comprehensive survey. Only 47% would order imaging for a new type of headache, 31% for worsening headache, and 35% for a headache unresponsive to treatment. Only 28% were familiar with the American Academy of Neurology guidelines on preventive treatment and 40% were familiar with the Choosing Wisely Campaign recommendations on migraine treatment. Just 34% were aware that opioids can cause medication-overuse headache. Non-pharmacologic treatment was not usually recommended. PCPs favored educational opportunities involving direct contact with headache physicians (56%). Conclusions: PCPs are not universally aware of the specific recommendations for managing migraine patients. Future work should focus on innovative ways to provide decision support and education for PCPs caring for migraineurs.